Food Waste Generation and Economic Implications during Ramadan in Student Rented Houses: A Pilot Study - M.S.M Ghazali; M. Mupit; M.E. Azni; Zaihar Yaacob; K.N. Ibrahim; Mohamad Zulkeflee Sabri; Mohd Nizam b Zahari; A.A Hamzah (Penerbit Jurnal Indonesia, 2025)
Food waste during Ramadan is a growing concern in Malaysia, with limited research on university students in rented accommodations. This pilot study examined their food waste generation using a mixed-methods approach: daily quantitative measurements and qualitative interviews on food practices. Findings showed students produced 0.25 kg/person/day, lower than urban households, yet about 40% of food prepared or purchased was discarded, with some households food waste discarded reaching up to 65%. Waste levels varied by household size, purchasing behavior, and eating habits, influenced by the dual-meal Ramadan pattern. Minimal sustainable practices were observed, highlighting the need for awareness and behavioral interventions. Limbah makanan selama Ramadan menjadi perhatian serius di Malaysia, dengan penelitian terbatas pada mahasiswa yang tinggal di rumah sewa. Studi awal ini meneliti timbulan sampah makanan melalui pendekatan campuran: pengukuran kuantitatif harian dan wawancara kualitatif tentang praktik konsumsi. Hasil menunjukkan mahasiswa menghasilkan 0,25 kg/orang/hari, lebih rendah dibandingkan rumah tangga perkotaan, namun sekitar 40% makanan yang disiapkan atau dibeli terbuang, dengan beberapa rumah tangga sampah makanan yang dibuang mencapai hingga 65%. Tingkat pemborosan bervariasi menurut ukuran rumah tangga, perilaku belanja, dan pola makan, dipengaruhi pola dua kali makan Ramadan. Praktik berkelanjutan minimal, menegaskan perlunya kesadaran dan intervensi perilaku.